Administrowanie hurtowniami danych w środowisku przetwarzania gridowego - Owoc, Mieczysław L.; Pondel, Maciej (Data warehouse administration using grid computing, 2006)
Announced progress of data processing effectiveness in grid technology environment is strictly tied to warehouse administrator's (WHA) functions . The main goal of the paper is to point out key WHA functions can be supported by grid computing and analysis of two of them: monitoring and tunning apart of presentation data warehouse contents. Practical aspects of the problem are presented using Oracle 1 Og serwer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 123-132